Geomarketing para la identificación de zonas potenciales en el sector farmacéutico de las localidades de Suba y Usaquén (2023)
In any type of business that depends on direct sales to the consumer at a physical point, the concern always arises about how to choose the best location for the commercial premises. Therefore, this document seeks to identify, in a technical and objective way, using geographical tools and measurement techniques. Geomarketing, these areas with the greatest potential and probability of success in the pharmaceutical or medicine sales market. This analysis was carried out in the study area limited to the towns of Suba and Usaquén in the city of Bogota.